Working Together Pays Dividends for Official Language Minority Communities! - Quebec English-language Production Council; Quebec Community Groups Network (QCGN); English Language Arts Network (ELAN); Alliance nationale de l'industrie musicale; Alliance des producteurs francophones du Canada (APFC); Fédération culturelle canadienne-française (FCCF) (2022)

Un comité de la Chambre des communes vote pour l’abandon des Québécoises et des Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Suggesting Change : The Situation of the English-speaking Minority of Quebec and Proposals for Change - Quebec Community Groups Network (QCGN) (2002)
Actions by the Government of Canada, such as the Speech from the Throne in January 2001, the nomination of Minister Stéphane Dion to coordinate the Federal Government's policy on official languages and chair the team of Ministers directly involved in Official Languages Policy and Program and his desire to develop an action plan to support the application of the Official Languages Act are encouraging. The demonstration of the political will of the Government to fulfill its obligation to ensure the full support of the development of vibrant and healthy Official-language minority communities throughout Canada is absolutely essential. It is, thus, incumbent on the Government that there is understanding and acceptance of the needs and realities of each linguistic minority community by both the majority populations and by those within the Canadian Government whose job is to develop and implement policy in support of the Francophone and Anglophone minority communities. The Official Languages Act must ensure the means and mechanisms for coordinated action and mobilization of the necessary resources to empower official minority language communities. As such, the action plan put forward by Minister Dion must be aimed at enabling the English-speaking minority in Quebec to build its own capacity, using solid facts and broad-based knowledge to be able to work with all governments to maintain and develop strong, vibrant English-speaking communities throughout Quebec.

Strategic Intervention Plan : English Federal Correctional Services in Quebec - Quebec Community Groups Network (QCGN) (2021)

Resolution on the Definition of Quebec's English-speaking Community / Résolution concernant la définition de la communauté d'expression du Québec - Quebec Community Groups Network (QCGN) (2021)

Quebec Budget Must Address Underfunding of Our Community Groups : QCGN - Quebec Community Groups Network (QCGN) (2023)

QCGN Wraps Up Annual Meeting Resolved to be a Strong Voice for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

QCGN Statement on Bloc Québécois report on federal funding for Quebec’s English-speaking minority - Quebec Community Groups Network (QCGN) (2023)

QCGN Pleased with Renewed Support for English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2019)
Keywords: Official Language Minority Community (OLMC)

QCGN Looks Forward to Working Together with Premier François Legault and His New Cabinet - Quebec Community Groups Network (QCGN) (2018)

QCGN Expresses Serious Misgivings About Vague Government Consultation Plan - Quebec Community Groups Network (QCGN) (2019)

QCGN Congratulates Eric Girard, New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2022)

QCGN Calls on Premier Legault to Support English-speaking Community - Quebec Community Groups Network (QCGN) (2019)

QCGN Board Responds to Public Withdrawal of Board Members - Quebec Community Groups Network (QCGN) (2019)

QCGN Appearance before the House of Commons Standing Committee on Official Languages - Quebec Community Groups Network (QCGN) (2016)

Projet Accès à la justice en anglais : Accès aux sites Web du gouvernement du Québec en anglais : Rapport exécutif et recommandations - Quebec Community Groups Network (QCGN) (2023)
Le projet Accès à la justice en anglais du QCGN (« le Projet ») repère et recherche les domaines où la communauté d’expression anglaise éprouve des difficultés à accéder à ses droits en mettant l'accent sur l'accès des communautés aux services publics. Il utilise l'information comme une ressource stratégique pour comprendre et améliorer l'accès à la justice en anglais au Québec.

Petition demands rethink of Bill 15’s radical revamp of Health Care Network - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2017)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2018)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2019)

Network News - Quebec Community Groups Network (QCGN) (2020)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2021)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2022)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2023)

Network News - Quebec Community Groups Network (QCGN) (2024)

Mémoire présenté dans le cadre de la consultation prébudgétaire 2024-2025 - Quebec Community Groups Network (QCGN) (2024)

Mémoire présenté à la Consultation prébudgétaire mené par Eric Girard, ministre des Finances du Québec - Quebec Community Groups Network (QCGN) (2023)
Les section A à C de ce mémoire traitent des besoins de financement des organismes du secteur communautaire du Québec, et plus particulièrement des besoins des organismes qui offrent des services et des programmes aux Québécois d'expression anglaise. Le Quebec Community Groups Network (QCGN) a depuis longtemps le mandat de recueillir, de colliger et d'articuler les besoins de la communauté d'expression anglaise du Québec, et le travail que nous avons effectué dans ce dossier au cours des dernières années a considérablement éclairé ces sections de notre mémoire.

[Letter to House Leaders from Geoffrey Chambers, QCGN President] - Chambers, Geoffrey (2020)

Legislative Update, Bill C-13 An Act to Amend the Official Languages Act, to Enact the Use of French in Federally Regulated Private Businesses Act and to Make Related Amendments to Other Acts - Quebec Community Groups Network (QCGN) (2022)

Le QCGN félicite Éric Girard, nouveau ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le QCGN demande la nomination d’un ministre responsable des Relations avec les Québécois d’expression anglaise - Quebec Community Groups Network (QCGN) (2022)

Le QCGN clôture son assemblée annuelle, résolu à défendre haut et fort les droits des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Le Canada, le Québec et les accords intergouvernementaux à l'appui des Québécois d'expression anglaise - Quebec Community Groups Network (QCGN) (2023)

Le budget du Québec doit s'attaquer au sous-financement de nos groupes communautaires : QCGN - Quebec Community Groups Network (QCGN) (2023)

Lancement d’une pétition pour la révision de la réforme radicale du réseau de la santé prévue par le projet de loi 15 - Quebec Community Groups Network (QCGN) (2023)

House of Commons Committee Votes to Forsake English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Déclaration du QCGN sur le rapport du Bloc Québécois concernant le financement fédéral de la minorité d’expression anglaise du Québec - Quebec Community Groups Network (QCGN) (2023)

Community Leaders Ready to Assist Kathleen Weil, Quebec's New Minister Responsible for Relations with English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2017)

Community Leaders Demand Major Changes to Bill 10 - Quebec Community Groups Network (QCGN) (2014)

Canada, Quebec, and Intergovernmental Agreements to Support English-speaking Quebecers - Quebec Community Groups Network (QCGN) (2023)

Brief to the Pre-Budget Consultation Chaired by Finance Minister Eric Girard - Quebec Community Groups Network (QCGN) (2023)
Sections A to C of this brief address the funding needs of Quebec’s community sector organizations, and more specifically the needs of those organizations which provide services and programs to English-speaking Quebecers. The Quebec Community Groups Network (QCGN) has long held a mandate to collect, collate, and articulate the needs of Quebec’s English-speaking community, and the work that we have done on this file in recent years has informed these sections of our brief significantly.

Brief to the 2024-2025 Pre-budget Consultation - Quebec Community Groups Network (QCGN) (2024)

Access to Justice in English Project : Access to Quebec government websites in English : Executive Summary and Recommendations - Quebec Community Groups Network (QCGN) (2023)
QCGN’s Access to Justice in English project (“the Project”) identifies and researches areas where the English-speaking community are experiencing difficulty accessing their rights, with a strong focus on community access to public services. It leverages information as a strategic resource to understand and improve access to justice in English in Quebec.

Access to Justice for Minority Populations : Focus on the English-speaking Communities of Quebec: 2000-2016 - Shohet, Linda (Quebec Community Groups Network (QCGN), 2016)
The objectives of this project are to research access to justice issues experienced by English-speaking Quebecers from their perspective, to establish metrics for measuring access to justice that fit the needs of community members, and to make recommendations to mitigate or overcome gaps and challenges for the English-speaking community of Quebec. The guiding question is: What is the lived experience for an English-speaking Quebecer in accessing legal and judicial information and services or in interacting with any of the social services that are now understood to be implicated in the broader concept of access to justice? This literature review is the first deliverable from Phase 1 of the project with an expectation that the findings will inform the second deliverable — a research plan to fill gaps in knowledge about the reality of access to justice for the anglophone population of Quebec.

A New Multi-year Official Languages Plan to Support Canada’s English Linguistic Minority Communities - Quebec Community Groups Network (QCGN) (2016)
This aim of this document is to outline the strategic priorities of the English-speaking Community of Quebec (ESCQ), and its high-level expectations from a new multi-year Official Languages Plan to support Canada’s English linguistic minority communities. Sector and regional leaders have developed their own priorities and expectations, which the strategic priorities contained hereunder support.
Keywords: Official Language Minority Community (OLMC)